Fertility Cost, Intergenerational Labor Division, and Female Employment - Haiyue Yu; Jin Cao; Shulong Kang (Norges Bank, 2019)
China has set to increase the minimum retirement age, to ease the pressure from pension expenditure and the falling labor supply caused by the aging population. However, policy debates have so far neglected the crucial fact that families in China largely rely on retired grandparents for childcare. Using novel and high-quality survey data, we demonstrate that intrafamily downward labor transfer towards childcare significantly increases young females' labor force participation rate and their labor income, and such effects do not exist for males. Furthermore, we show that the positive effects from grandparental childcare are higher for better-educated, urban females with younger children. This paper thus reveals a large, hidden cost in the new retirement policy - the reduced feasibility of grandparental support, due to postponed retirements, may crowd out productive labor of young females, - and rationalizes a series of social protection policies to accompany the phase-in of the new retirement scheme.
hdl:11250/2581014
Keywords: C24; J13; J22; 330; intergenerational labor division; grandparental childcare; female employment; human capital accumulation; minimum retirement age